2008
DOI: 10.1080/15563650701397159
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of nail growth following Bajiaolian intoxication

Abstract: Bajiaolian (Dysosma pleianthum), a species in the Mayapple family (Podophyllum pelatum), has been widely used as a traditional Chinese herbal medication for the remedies of snake bite, tumor growth, post-partum recovery, and acne. It has also been used in western medicine, especially topically for various skin lesions. Both oral ingestion and dermal application may result in severe toxicity. The clinical presentations reported after Bajiaolian poisoning include nausea, vomiting, diarrhea, abdominal cramps, tac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Plants containing POD and its analogues were used in folk medicines as agents for treating snake bites [21], [43], cancer, viral infection and astriction [44]. Because of its poor selectivity and small therapeutic index, POD has been incriminated in many poisoning cases as a result of either overdose or accidental ingestion [14]–[16], [18], [19].…”
Section: Discussionmentioning
confidence: 99%
“…Plants containing POD and its analogues were used in folk medicines as agents for treating snake bites [21], [43], cancer, viral infection and astriction [44]. Because of its poor selectivity and small therapeutic index, POD has been incriminated in many poisoning cases as a result of either overdose or accidental ingestion [14]–[16], [18], [19].…”
Section: Discussionmentioning
confidence: 99%
“…Besides enterocolitis and sepsis, differential diagnosis of the typical colchicine toxidrome (gastroenteritis, hypotension, lactic acidosis, and prerenal azotemia) should include nonsteroidal antiinflammatory drug and metal poisoning (iron, arsenic, mercury). Without any knowledge of the ingested plant, the differential diagnosis is wider (summarized in Table 2) (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The patient was not able to walk without aid for several months after discharged from hospital and the rate of nail growth was declined greatly after Bajiaolian intoxication. After seven and half years it was found that patient had no need to cut her fingernail (Chou et al, 2008).…”
Section: Cessation Of Nail Growthmentioning
confidence: 98%